NILAI-NILAI PENDIDIKAN KELUARGA DALAM UU NO. 23 TAHUN 2002 TENTANG PERLINDUNGAN ANAK - hadi, abd (PSW, 2016)
This article examines the values of family education in Republic Act No. 23 of 2002 on the protection of children. Law on child protection are state regulations that have the force of law that guarantees the fulfillment of childrens rights in order to live, grow, develop, and participate optimally in accordance with human dignity and protection from violence and discrimination, in order to create quality child , noble